(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
Cooperatives have been evidently solicited to play a positively significant multifaceted role in the promotion of wellbeing among members hence, this study was conducted to examine the existing interrelationships between cooperative membership, farmers’ welfare, and farm production level along its determinants among layer egg producers in southwest Nigeria, using a multidimensional approach. A multistage sampling technique was employed in the collection of data from 185 poultry farmers; 94 Cooperators, and 91 Noncooperators, randomly from four local government areas, using well-structured questionnaires. Descriptive statistics, T-test, Variance inflation factor, Alkire-Foster multidimensional poverty measures, and multiple regression are employed in data analysis.: Many (54%) of the poultry farmers are medium scaled, within which a larger proportion of about 61% are cooperators. Also, the output of the cooperator category was found significantly higher than their non-cooperator counterpart by 128.1 % crates per day at 5 % probability level. Furthermore, there exists a veritable positive relationship between farmers’ multidimensional welfare and increased production scale, while years of farming experience, farming as a primary occupation, farm size, and cooperative membership, significantly influence increased output. The finding showed that farmers’ multidimensional poverty headcount indices are inversely proportional to their scale of production. There also exists a significant positive relationship between increased production scales, cooperative membership, and farmers’ welfare statuses.